Quantitative stability estimates for a two-phase Serrin-type overdetermined problem. (September 2022) - Cavallina, Lorenzo; Poggesi, Giorgio; Yachimura, Toshiaki
Abstract: In this paper, we deal with an overdetermined problem of Serrin-type with respect to a two-phase elliptic operator in divergence form with piecewise constant coefficients. In particular, we consider the case where the two-phase overdetermined problem is close to the one-phase setting. First, we show quantitative stability estimates for the two-phase problem via a one-phase stability result. Furthermore, we prove non-existence for the corresponding inner problem by the aforementioned two-phase stability result.